VET and the “Competency-Tetris”: Inclusion of Whom, to What, and Where? - Rosenblad, Niklas; Schaffar, Birgit; Löfström, Erika (Nordic Journal of Comparative and International Education (NJCIE), 2022)
The purpose of the article is to empirically analyse how the idea of inclusion is portrayed within the boundaries of the “Competency-Tetris”: a metaphor that should not be confused with the Tetris® game but used to theoretically capture individualised, competency-based, and managerially governed Vocational Education and Training (VET). We argue that the meaning of social inclusion within and through VET is unclear and vested by the human capital doctrines and the neoliberal assumptions from which it is derived. Whom does inclusion in VET involve, and to what and where does inclusion take place? Employing a design-based research approach, we used abductive applications to analyse data produced through participatory ethnographic observations (N=32) and interviews (N=12). The results identified four abstracted themes: (1) Fitting the workforce auction; (2) Multi-professional support trajectories; (3) Inclusion of qualification measures; and (4) Social and cultural learning communities. The first three abstracted themes suggest that the Competency-Tetris is a social divider of students based on a “go-forward” engine with social engineering at its fore. That is, the desired boundaries between VET and work are not strengthened, and the question of enabling equal learning for all students faces a U-turn. Thus, the economic value accumulated in competency-based qualification measures is accentuated. The latter abstracted theme identifies a different, albeit obscured, aspiration: human encounters requiring dignity, mutual respect, social generosity, and developmental sustainable ecology are increasingly approached as part of, within, and through VET.